Making it happen: How managerial actions enable project-based ambidexterity. Issue 2 (April 2016) - Turner, Neil; Swart, Juani; Maylor, Harvey; Antonacopoulou, Elena
The literature on ambidexterity is dominated by theoretical development and does not fully explain how ambidexterity is enacted. There is limited focus on the managerial actions in day-to-day operations that enable this important phenomenon. We posit that projects offer an ideal context to investigate the actions that enable ambidexterity since they necessarily combine planning and control (exploitation) with some degree of novelty (exploration). Using extensive data from eight project-based case studies in the Information Technology services sector, we ask the research question, How is project-based ambidexterity enabled? Within this context, we identify two different types of project-based ambidexterity ( distributed and point ambidexterity) and five managerial actions ( buffering, gap-filling, integration, role-expansion and tone-setting ) that enable ambidexterity. We investigate the underlying resource utilisation in terms of intellectual capital (namely, human, social and project capital) and show the complexity of their interplay in achieving ambidexterity. Finally, we develop a model that brings these concepts together and identify how the 'integration' function is central to, and interwoven with, the other actions.